2017
DOI: 10.1080/10522158.2017.1410267
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing relationship skills and couple functioning with mobile technology: An evaluation of the Love Every Day mobile intervention

Abstract: A research-informed mobile application (app) was created to encourage and activate couples to demonstrate healthy relationship behaviors in an effort to promote relationship quality, stability, and resilience. The app, , is grounded in the literature on couple quality, habit formation, and family resilience, and it uses tenets of effective behavioral intervention technologies. Forty-three couples ( = 86 participants) engaged with the app across a 21-day period and completed online evaluations, which consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 65 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…Important developments in the CRE field are documented by several valuable reviews (e.g., Markman et al, 2019;Stanley et al, 2020) as well as important meta-analytic studies (e.g., Hawkins & Erickson, 2015;Lucier-Greer & Adler-Baeder, 2012). These reviews of CRE have documented how participation in educational interventions, on average, helps both advantaged and disadvantaged couples strengthen relationship skills and increase satisfaction, but also pointed out critical gaps in the field and areas of needed improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Important developments in the CRE field are documented by several valuable reviews (e.g., Markman et al, 2019;Stanley et al, 2020) as well as important meta-analytic studies (e.g., Hawkins & Erickson, 2015;Lucier-Greer & Adler-Baeder, 2012). These reviews of CRE have documented how participation in educational interventions, on average, helps both advantaged and disadvantaged couples strengthen relationship skills and increase satisfaction, but also pointed out critical gaps in the field and areas of needed improvement.…”
Section: Introductionmentioning
confidence: 99%
“…As flexible delivery options continue to grow in popularity in providing RE (Lucier-Greer et al, 2018), practitioners may find using online module content similar to what was presented in this study beneficial for working with participants. Those interested in the methods used in this study are encouraged to contact the authors.…”
Section: Implications For Practitioners Researchers and Policy Makersmentioning
confidence: 96%
“…Flexible-delivery RE programs are also increasing in popularity and effectiveness (McAllister, Duncan, & Hawkins, 2012). Recent reports show that an online RE program had a positive effect on relationship satisfaction and communication skills (Knopp & Rhoades, 2018), and a mobile app-based RE program enhanced relationship quality, skills, and behaviors (Lucier-Greer, Birney, Gutierrez, & Adler-Baeder, 2018).…”
Section: Online Resources and Relationship Servicesmentioning
confidence: 99%
“…Health Technol 2021 | http://dx.doi.org/10.21037/ht-20-28 services and information for parents who are difficult to reach through typical methods (pamphlets, consultations, and classes) due to geographical barriers, time constraints, and stigma (31,32,57). This literature review found several apps that were specifically developed for disadvantaged or vulnerable populations such as military and low-income fathers (34); mothers living in rural and remote areas (47); high-risk mothers (56); parents with low socioeconomic status (43,50,60,61); refugees (62); and areas of low internet connectivity (63).…”
Section: Theme #3 Apps Developed To Overcome the Digital Dividementioning
confidence: 99%